Formation damage using palm oil ester based drilling fluid - Md., A. A. (Faculty of Chemical and Natural Resources Engineering, 2008)
Oil-based drilling fluids are widely used in drilling, especially in highly deviated welIs. This is because oil-based drilling mud systems perform much better than water-based muds in bore hole stabilization and providing lubricity thereby give faster rates of penetration. However, they are a cause for environmental concern and with the potential long-term liability for damage caused by mud spills and problems in disposal of the oilcontaminated drill cuttings. As environmental legislation and controls become more stringent, even the newer and less polluting mineral and synthetic oils in used now may be adjudged unsuitable because of their non-biodegradability. In direct response to the need for a high performance and environmentalIy safe alternative to petroleum-based materials, common vegetable and fish oils have been tested . However, none of them as yet offers the necessary chemical stability nor rheological properties required. After considerable research and extensive testing , a high performance and biodegradable vegetable-based ester has been produced from palm kernel oil. This ester has been produced in Malaysia since 1995 and has found widespread acceptance and applications in offshore regions where pressure from the environmental authorities has been mounting. The result shows that the performances of the formulated invert emulsion palm oil ester (OMC 586) oil-based mud system are comparable to the Sarapar Oil-based Mud system. The degree of damage done by both mud systems only shown a light difference. However, the filtration properties of OMC 586 Ester Oil-based Mud system has shown a greater loss volume, but not in a severe condition.